EFFECT OF FOLIAR SPRAYING WITH HUMIRON ON GROWTH AND YIELD OF TWO SWEET PEPPERS HYBRID ( CAPSICUMANNUUM L. ) IN OPEN FIELD - SAEID, ABDULJEBBAR I.; F, SUHAILA RAFEEQ; D, OMEED MOHAMMAD; ASWAD, SAAD YOUSF (Journal of Duhok University, 2021)
This investigation was carried out in Malta research farm, Dohuk government, Kurdistan region / Iraq, in summer season 2019 in open filed to study theeffect of Humiron on growth and yield of two peppers Hybrid ( California wonder and Gulpiner). The results show thathybridGulpinerhad asignificant variance in plant high, superior in branches number, California wonder was significant difference in fruit number,fruit weight, yield per m2and total yield t.ha-1.Humiron provided the highest value in number of branches at highest level of Humiron and vitamin C, fruits number per plant, and totalyield t.ha-1.